2015
DOI: 10.3389/fpsyg.2015.00480
|View full text |Cite
|
Sign up to set email alerts
|

Adults with sensorimotor disorders: enhanced physiological and psychological development following specific sensorimotor training

Abstract: The aim of the study was to investigate, for the first time, if it is possible to integrate primary reflexes in adults with sensorimotor disorders through sensorimotor therapy (SMT). Participants consisted of 14 adults, one man and 13 women, with an average age of 35 years who completed a SMT program over 3 years. They were compared with a reference group of 100 youngsters spanning from 11 to 17 years. Procedures were the same for both youngsters and adults including regular visits to a therapist and training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 61 publications
(103 reference statements)
8
41
0
Order By: Relevance
“…Research has to an inceasing degree presented associations with learning difficulties [ 10 ], problems of concentration, language impairment, behavior problems, overarching academic difficulties (reading and writing), poor social skills, anxiety, depression [ 11 ], mental health difficulties, [ 12 ] and peer victimization [ 13 ]. Studies have also shown that motor difficulties are not outgrown [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has to an inceasing degree presented associations with learning difficulties [ 10 ], problems of concentration, language impairment, behavior problems, overarching academic difficulties (reading and writing), poor social skills, anxiety, depression [ 11 ], mental health difficulties, [ 12 ] and peer victimization [ 13 ]. Studies have also shown that motor difficulties are not outgrown [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some children with this diagnosis also exhibit a different kind of anomalous motor ability believed to constitute neurodevelopmental immaturities or neurological soft signs (NSS) rather than neurological abnormalities [ 17 ]. NSS is a heterogenous mix of movement patterns, some of which are remaining primary reflexes [ 15 ] and possibly also defective sensory integration [ 21 ]. The European Academy of Childhood Disability (EACD) [ 19 ] as well as Wiener-Vacher and colleagues [ 22 ] recommended that sensory status (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further notion is that ice hockey requires an outstanding balance ability Psychology (Han, Anson, Waddington, Adams, & Liu, 2015) which is particularly important in situations that require attention and concentration (Hrysomallis, 2011) as in shootouts. Therefore further studies are also suggested to investigate the role of sensorimotor maturity (Niklasson, Rasmussen, Niklasson, & Norlander, 2015;Niklasson, Norlander, Niklasson, & Rasmussen, 2017).…”
Section: Discussionmentioning
confidence: 99%